2019
DOI: 10.2217/fon-2019-0374
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium SPP : The Promising Trojan Horse in the Era of Precision Oncology

Abstract: Selective delivery of therapeutic agents into solid tumors has been a major challenge impeding the achievement of long-term disease remission and cure. The need to develop alternative drug delivery routes to achieve higher drug concentration in tumor tissue, reduce unwanted off-target side effects and thus achieve greater therapeutic efficacy, has resulted in an explosive body of research. Bifidobacterium spp. are anaerobic, nonpathogenic, Gram-positive bacteria, commensal to the human gut that are a possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…Beyond academia, Dr Sharma pursues interests such as paragliding and hiking. and acidic tumor environments, thereby prompting attempts to engineer bacteria, such as Escherichia coli, 9,10 Bifidobacterium, 11,12 and Salmonella, 13,14 as controllable nanorobotic vehicles to deliver therapeutic payloads for solid tumor treatment. 15 On the other hand, magnetic hyperthermia-based cancer therapy (MHCT) relies on the ability of magnetic nanoparticles (MNPs) to induce heat in response to an external alternating current magnetic field (AMF).…”
Section: Deepika Sharmamentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond academia, Dr Sharma pursues interests such as paragliding and hiking. and acidic tumor environments, thereby prompting attempts to engineer bacteria, such as Escherichia coli, 9,10 Bifidobacterium, 11,12 and Salmonella, 13,14 as controllable nanorobotic vehicles to deliver therapeutic payloads for solid tumor treatment. 15 On the other hand, magnetic hyperthermia-based cancer therapy (MHCT) relies on the ability of magnetic nanoparticles (MNPs) to induce heat in response to an external alternating current magnetic field (AMF).…”
Section: Deepika Sharmamentioning
confidence: 99%
“…Flagellated bacteria which exhibit self-propulsion in response to environmental, physical and chemical stimuli represent promising candidates as hypoxia targeting self-propelling agents. 6–8 Notably, several facultative and obligate anaerobes have a natural preference for growing and colonizing hypoxic and acidic tumor environments, thereby prompting attempts to engineer bacteria, such as Escherichia coli , 9,10 Bifidobacterium , 11,12 and Salmonella , 13,14 as controllable nanorobotic vehicles to deliver therapeutic payloads for solid tumor treatment. 15…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported using Bifidobacterium spp. for its anti-tumor activities [135]. Although these microorganisms successfully colonize tumor cells, anti-tumor effects of Bifidobacterium have not yet been fully determined.…”
Section: Bifidobacterium Sppmentioning
confidence: 99%
“…Bifidobacteria represent less than 10% of the intestinal microbiome [ 32 ]. Among other things, they promote the digestive process and have the potential to synthesize certain vitamins (e.g., vitamin B6, folic acid, and thiamine) and reduce toxic metabolites [ 33 ]. Just like Lactobacilli , they ferment glucose to lactic acid, which stabilizes the acid environment in the intestine to a constant pH (<5).…”
Section: Theoretical Backgroundmentioning
confidence: 99%